PARADIGM SEMANTIC WEB IN THE CONTEXT OF DIGITAL LIBRARY: SERVICES AND INFORMATION INTEGRATION - Novytskyi, O. (International Journal of Computing, 2014)
This paper presents a several of theoretical ideas and applied technology that can be embodied in the creation of Semantic Digital Library (SDL). In particular, considerable attention paid to how the Semantic Web technology is used in various aspects of DL. A basic level in the DL that may be carriers of semantic description. Described the advantages of this approach. It also highlights issues that arise during the integration of classical electronic libraries and Semantic Web a place in these processes. Made a brief overview of the world’s leading projects to create DL using Semantic Web.